2013
DOI: 10.1186/1477-9560-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human soluble thrombomodulin administration improves sepsis-induced disseminated intravascular coagulation and mortality: a retrospective cohort study

Abstract: BackgroundEarly treatment of disseminated intravascular coagulation (DIC) can be associated with improved patient outcomes. The Japanese Ministry of Health and Welfare (JMHW) and the International Society on Thrombosis and Haemostasis (ISTH) criteria are the most specific for diagnosis of septic DIC. The revised Japanese Association for Acute Medicine (JAAM) criteria are able to diagnose sepsis-induced DIC in the early stage. Recombinant human soluble thrombomodulin (rhTM) has recently been used for treating D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
3
23
2
Order By: Relevance
“…Another 2 retrospective studies of sepsis-induced DIC reported similar results [11,15]. In our study, the platelet counts had significantly improved by day 7 in the rhTM group, whereas a similar response was not observed in the GM group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another 2 retrospective studies of sepsis-induced DIC reported similar results [11,15]. In our study, the platelet counts had significantly improved by day 7 in the rhTM group, whereas a similar response was not observed in the GM group.…”
Section: Discussionsupporting
confidence: 86%
“…Several previous retrospective studies have reported that rhTM treatment yielded improved survival rates, compared with those in the control group without rhTM [9,11,15]. Although in this study the mortality of rhTM was similar to that of the GM group.…”
Section: Discussioncontrasting
confidence: 43%
“…Recently, the safe use of rTM for ICU patients has been reported in a phase IIb study of rTM [3]. Another study had shown that rTM may be superior to conventional DIC treatments in patients in the ICU [4]. However, the optimal timing of rTM administration has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with rhs-TM has been reported to improve the prognosis of patients with sepsis-induced DIC without increasing bleeding risk 23) 24) , and administration of rhs-TM was found to reduce 28-day mortality rate in patients with DIC associated with severe sepsis 25) . These results show the efficacy of rhs-TM for patients with DIC associated with infectious diseases.…”
Section: Discussionmentioning
confidence: 99%